Interleukin-10 and Transforming Growth Factor Beta1 Gene Polymorphisms in Chronic Heart Failure - Mahmoudi, Mohammad Jafar; Hedayat, Mona; Taghvaei, Mohammad; Harsini, Sara; Nematipour, Ebrahim; Rezaei, Nima; Farhadi, Elham; Mahmoudi, Maryam; Sadr, Maryam; Esfahanian, Nilufar; Nourijelyani, Keramat; Amirzargar, Ali Akbar (Acta Biomedica Atenei Parmensis, 2019)
Background: As cytokines, including interleukin-10 (IL-10) and transforming growth factor beta 1(TGF-β1) seem to contribute towards the pathogenesis of chronic heart failure (CHF), this study was performed to assess the associations of certain single nucleotide polymorphisms (SNPs) of these genes in a case control study. Methods: This investigation was carried out to determine the frequency of alleles, genotypes and haplotypes of TGF-β1 and IL-10 single-nucleotide polymorphisms (SNPs) in 57 Iranian patients with CHF compared with 140 healthy subjects using polymerase chain reaction with sequence-specific primers method. Results: Results of the analyzed data divulged a negative association for both TGF-β1 GC genotype at codon 25 (P=0.047) and CT genotype at codon 10 (P=0.018) and CHF proneness. Although, TGF-β1 CC genotype at codon 10 was found to be positively associated with CHF (P=0.011). Moreover, the frequency of IL-10 (−1082, -819, -592) ATA haplotype and TGF-β1 (codon 10, codon 25) TG haplotype were significantly lower in the patients group (P=0.004 and P=0.040, respectively), while TGF-β1 (codon 10, codon 25) CG haplotype was overrepresented in patients with CHF (P=0.007). Conclusions: Cytokine gene polymorphisms might affect vulnerability to CHF. Particular genotypes and haplotypes in IL-10 and TGF-β1 genes could render individuals more susceptible to CHF.